Deepfake: A Review from The Victimology Perspective - Noviantama, Doni; Rahman, Alif Alfani (Contemporary Issues in Criminal Law, 2025)
This study focuses on deepfake as a result of synthetic media that can change a person’s image, speech, or actions by utilizing artificial intelligence, which results in heavily realistic outcomes that make someone seem to be doing something when in fact they are not. Thus, it is detrimental to the victim whose face has been manipulated using the deepfake. This study will analyze the characteristics of deepfake, what crimes are born out of deepfake, and how the regulations for victim protection are related to the use of deepfake. The purpose of this study is to determine the characteristics of deepfake, the crimes that come out of it, and the regulations for victim protection relating to the use of deepfake. The method used is normative legal research with a conceptual approach, a statutory approach, and a case study approach. The results of this study indicate that the first characteristic of deepfake is a synthesis technique created using AI, deepfake is made using a person’s face as if the person is doing something, the person’s face is manipulated without consent, and the results of the manipulation are highly realistic. Then the crimes that arise from deepfakes are pornography, defamation, spreading fake news, fraud, and using other people’s personal data without consent. Meanwhile, the protection of deepfake victims is regulated in the Protection of Witnesses and Victims Law, Human Rights Law, Criminal Procedure Code, Government Regulation No. 7 of 2008 in conjunction with Government Regulation No. 35 of 2020 and Regulation of the Minister of Communication and Information Number 5 of 2020 on the Implementation of Private Electronic Systems (Permenkominfo-PSELP). Where victims have the right to make reports/complaints, submit restitution requests, and request a takedown of the deepfake content. Keywords: Artificial Intelligence, Deepfake, Victim Abstrak Penelitian ini berfokus pada deepfake sebagai hasil media sintesis yang dapat mengubah citra, ucapan, atau tindakan seseorang dengan memanfaatkan artificial intelligence yang hasilnya sangat realistis yang membuat seseorang seolah-olah sedang melakukan sesuatu padahal aslinya tidak. Sehingga merugikan korban yang wajahnya telah dimanipulasi menggunakan deepfake tersebut. Penelitian ini akan menganalisis tentang bagaimana karakteristik deepfake, tindak pidana apa saja yang lahir dari deepfake dan bagaimana regulasi perlindungan korban dalam kaitannya dengan penggunaan deepfake. Tujuan penelitian ini adalah untuk mengetahui bagaimana karakteristik deepfake, tindak pidana apa saja yang lahir dari deepfake dan bagaimana regulasi perlindungan korban dalam kaitannya dengan penggunaan deepfake. Metode yang digunakan adalah penelitian hukum normatif dengan pendekatan konseptual, pendekatan perundang-undangan, dan pendekatan kasus. Hasil penelitian ini menunjukkan bahwa karakteristik deepfake yang pertama yaitu teknik sintesis yang dibuat menggunakan AI, deepfake dibuat menggunakan wajah seseorang seolah-olah orang tersebut sedang melakukan sesuatu, wajah orang tersebut dimanipulasi tanpa izin serta hasil manipulasinya sangat realistis. Kemudian tindak pidana yang lahir dari deepfake adalah tindak pidana pornografi, pencemaran nama baik, penyebaran berita bohong, penipuan dan penggunaan data pribadi orang lain tanpa izin. Sedangkan regulasi perlindungan korban deepfake diatur dalam UU PSK, UU HAM, KUHAP, PP 7/208 jo PP 35/2020 dan Permenkominfo-PSELP. Dimana korban berhak untuk membuat laporan/pengaduan, mengajukan permohonan restitusi dan meminta untuk dilakukan takedown terhadap konten deepfake tersebut. Kata kunci: Deepfake, Kecerdasan Buatan, Korban